Quality Difference Analysis of Jujube Wine of 13 Varieties - Rong YIN; Qianru ZHANG; Junyu WANG; Zhihong LIANG (Shipin gongye ke-ji, 2023)
In order to study quality difference of jujube wine of different jujube varieties, 13 common varieties in the market were collected for fermentation. Basic physical and chemical indexes of the wine were determined, and organic acid and aroma components were also determined by ion chromatography and headspace solid phase microextraction-gas chromatography-mass spectrometry method respectively, and were then analysed combining with sensory evaluation. It was showed that contents of dry extract, VC and glycerol were all high, citric acid, succinic acid, lactic acid, acetic acid and quinic acid were the common organic acids, and esters were the main aroma components in different jujube wines. Different jujube wine had different quality characteristics. Fuping jujube wine, Yuanling jujube wine and Hami jujube wine had advantage in orgainic acid, Lingwu long jujube wine, Jixin jujube wine and Lingbao jujube wine had advantage in aroma components, and Goutou jujube wine had better basic physical and chemical indexes. Whereas, Lingwu long jujube, Jixin jujube and Goutou jujube were identified as the best jujube varieties for brewing by sensory evaluation, which indicated their wines had the best balance of flavor substances, and through analysis the common characteristics including sugar-acid ratio less than and mostly closing to 1, 6 kinds of different organic acid, more kinds of characteristic aroma substances, one dominant organic acid and more than two dominant aroma components which could contribute favourable flavor properties contained.